TERAPI PSIKOLOGIS BERBASIS ONLINE UNTUK MENURUNKAN TEKANAN DARAH PADA KLIEN DENGAN HIPERTENSI : STUDI LITERATUR - Handoyo, Lukman (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Psychological therapy is one of the most important aspects of management to reduce stress and control blood pressure for clients with hypertension. However, the implementation of psychological therapy faces challenges in being able to be given online in order to meet dynamic health services in the transitional era of the COVID-19 pandemic-endemic. The aim of this study was to explore various types of psychological therapies that can be implemented online-based to reduce blood pressure for hypertensive clients. This study was a traditional literature review that elaborates on previous research articles for thematic analysis. Article search was conducted in a semi-structured approach using predefined keywords and three academic databases: Scopus, PubMed, and CINAHL. The search results obtained six articles that form four themes: 1) Digital-Based Meditation Lowers Blood Pressure; 2) Digital-Based Mindfulness Lowers Blood Pressure; 3) General Therapeutic Lowering Blood Pressure; 4) Empowering Mind and Behavior by Online-Based Lowering Blood Pressure. Types of psychological therapy that are proven to reduce blood pressure in clients with hypertension including: meditation, mindfulness therapy, behavioral therapy, and counseling centered on client empowerment. Health workers who act as therapists (such as family/community nurses) need to consider the appropriate duration, type, and implementation strategy if they want to develop online-based psychological therapy applications for hypertensive clients.